A Conceptual Framework for Genetic Policy: Comparing the Medical, Public Health, and Fundamental Rights Models - Lori B. Andrews (Washington University Law Quarterly, 2001)
This Article presents the first attempt to develop a comprehensive legal framework governing the regulation of genetic information in the United States. Part II addresses the need for such legal framework. Part III analyzes three conceptual legal models that have been adopted in the past for regulating medical services: the medical model, the public health model, and the fundamental rights model. Part IV examines the results of medical and social scientific studies on the impact of genetic services. Part V addresses the impact of genetic services. Part VI revisits the three models to determine which is appropriate for genetics. Part VII discusses the legal justification for the fundamental rights model.
Keywords: Bioethics; Genetic screening; Discrimination against people with disabilities; Human Genome Project; Genetic testing; Genetics